ANALISIS IMPLEMENTASI KURIKULUM MERDEKA DALAM PEMBELAJARAN TEMATIK DI SEKOLAH DASAR - Hasibuan, Amir Mahmud; Tania Eviana, Nursari Wahyuni Sigalingging, Alya Sania Putri, Siti Annisa, Asiah Ramadhani. (Jurnal Inovasi Sekolah Dasar, 2026)
This research aims to identify the impacts and challenges faced by teachers and students when implementing this new curriculum. Merdeka Curriculum emerged as an innovation in Indonesian education, where the learning approach focuses on students' freedom to explore, follow their interests, and adapt learning methods to their needs. By adopting the concept of interactive and contextualized learning, teachers are expected to develop flexible and engaging teaching modules, which support students' active engagement. Although this curriculum offers various opportunities to improve the quality of learning, this study also found significant constraints, including teachers' lack of understanding of the preparation of teaching modules and limited adequate educational resources. In conclusion, despite the challenges in implementing Merdeka Curriculum, its positive impact on student engagement and understanding suggests the need to support this initiative through ongoing teacher training and resource development.